Konsumsi Tablet Tambah Darah dan Anemia Pada Remaja Putri Kota Bima, Nusa Tenggara Barat - Alawia, Fuji Astuti; Lestari, Pudji; Amalia, Rize Budi; Setyowati, Dewi (Yayasan Jompa Research and Development, 2025)
Anemia among adolescent girls remains a significant public health issue. Objective: This study aims to analyze the factors associated with anemia among adolescent girls in one of the vocational high schools (SMK) in Bima City. Methods: This research employed an observational analytic design with a cross-sectional approach. It was conducted from October 2024 to May 2025 at a vocational high school in Bima City, with the study population comprising 10th-grade adolescent girls. A total sampling technique was used, resulting in 122 respondents aged 14–17 years. Data were collected through questionnaires, anthropometric measurements, and hemoglobin level testing using the Point of Care Testing (POCT) method. Data were analyzed using the chi-square test. Results: The analysis showed significant associations between anemia and nutritional status (p=0.001), eating habits (p=0.012), iron supplement consumption (p=0.001), and medical history (p=0.021). No significant association was found between anemia and age at menarche (p=0.393), menstrual cycle (p=0.245), or duration of menstruation (p=0.342). Conclusion: Factors associated with the incidence of anemia among adolescent girls at one of the vocational high schools in Bima City include nutritional status, eating habits, iron supplement consumption, and medical history. Keywords: anemia, adolescent girls, nutritional status, eating habits, iron supplements